Pendidikan Jasmani dan Olahraga di Sekolah Dasar Menuju Gaya Hidup Bersih dan Sehat - Alfia Usmi Latifah; Aulia Marhamatun Nufus; Naufal Latifah; Nazwa Putri Rizkita; Putri Khairunnisa (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
Every human being has the right to shape himself into a healthy human being so that he can move well. Of course, being healthy must be familiarized from a young age. Elementary school age is an important period because at this age children are very vulnerable to various diseases and health problems. Diseases and health problems that often affect elementary school children are generally related to clean and healthy living habits, such as toothache, diarrhea, worms, skin diseases, dengue fever, and many others. This research uses the literature method obtained from scientific journal sources to provide an overview of how physical education and sports help elementary school children to improve clean and healthy living behavior. The results obtained are that there are components that support a clean and healthy lifestyle. Then internal and external factors must be considered because they can affect the increase in clean and healthy lifestyles. There are also simple steps that can be applied by elementary school-age children, such as the steps of washing hands every day and brushing teeth properly and correctly so that they can familiarize themselves with clean and healthy living.